Harmonization of the rome statute in the establishment of a human rights court in Indonesia - Nunung Rahmania; Atika Zahra Nirmala (Institute Of computer Science (IOCS), 2023)
The establishment of a Human Rights Court is necessary as there are gross violations of human rights in a country including Indonesia. Indonesia has harmonized the Rome Statute which is considered as the spearhead of the establishment of the Human Rights Court in Indonesia so that law enforcement against gross violations of human rights can be implemented. Therefore, this study aims to analyze and find out about the form of legal harmonization in the Human Rights Court in Indonesia and how the implementation and enforcement of law in the Human Rights Court in Indonesia. The type of research used is normative using a statutory approach and a case approach which is then analyzed descriptively and qualitatively. The results showed that the Harmonization of the Rome Statute in the establishment of the Human Rights Court in Indonesia was carried out partially or there were differences or deviations from the Rome Statute, namely in the Human Rights Court in Indonesia only regulates crimes against humanity, genocide, and the Ad Hoc Human Rights Court established under the Human Rights Court Law. The form of implementation and enforcement in cases of gross violations of human rights in the Human Rights Court in Indonesia has not been running properly because there are still several cases of gross violations of human rights that have not been handled until now.